Oxygenated Boron Species Generated In Situ by Protonolysis Enables Precision Synthesis of Alternating Polyesters - Luo, Huitong; Zhou, Yubo; Li, Qingtao; Zhang, Boru; Cao, Xiaodong; Zhao, Junpeng; Zhang, Guangzhao (Macromolecules, 2023)
Recently, Lewis pairs composed of organobases and organoboranes have shown high catalytic activity for the synthesis of polyethers by ring-opening polymerization of epoxides. Surprisingly, copolymerization of cyclic anhydride and a large excess of epoxide we conducted at elevated temperatures were free of polyether formation when catalyzed by a phosphazene base and triethylborane (Et3B), even after complete anhydride consumption. As a result, polyesters with (near) perfect alternating sequence distribution, controlled and narrowly distributed molar mass were readily obtained. Experimental and calculational results attributed the unexpected chemoselectivity to the protonolysis of Et3B and the newly formed oxygenated boron species. Most importantly, the reversible interchange of acyloxyborane and borinic ester at the propagating chain ends suppressed the reaction between hydroxy species and epoxide (formation of ethers) while maintaining the catalytic activity for the reaction between carboxy species and epoxide (formation of esters). The polyesters containing catalyst residues exhibited good cytocompatibility despite these changes. The in situ structure and activity evolvement of boron species revealed here will pave new pathways for rational design of metal-free catalysts.